Legislation and its impact on curbing human organ trafficking Qatari Law No. 15 of 2015 regarding the regulation of the transfer and transplantation of human organs as a model - Al Iftaihat, Yassir; Qaminassi, Imad Mustafa (Research Journal in Advanced Humanities, 2025)
This paper will make provisions on legislation and the effort towards halting human organ trafficking concerning Qatar’s Law No. 15 of 2015 as modern legislation. Among its chief objectives, the law sets out to control transactions and transplants of organs and defend the donor’s rights, proposing that for any transplant operation, the donor should be fully aware of the implications and be given a right to rescission. The study also shows the role of local and international legislation in combating the issues of the black market of organs and Qatari law, which is a successful example of finding the middle ground in achieving the maximum therapeutic impact while minimizing the potentially dangerous risks. The study’s findings also indicate that Qatari law should be followed by other legislations, which should also include the recommendation of increasing the range of countries and creating international organizations for cooperation to adapt legal rules for the model to the world. It also affirms the need to improve the performance of the law through increasing medical research to supply human organs and acknowledging that organ transplantation is an exceptional, sophisticated therapeutic exercise that does call for strict consciousness of the risks and returns. The study also shows that Qatar’s Law no. 15 / 2015 is a successful example of achieving the therapeutic interest and, at the same time, protecting the individuals, and it is helpful to eliminate the buying-selling of organs and tissues while respecting the principles of justice and human rights.